Localisation of mineralised tissue in a complex spinner flask environment correlates with predicted wall shear stress level localisation - Feihu Zhao (European Cells and Materials, 2018)
Spinner flask bioreactors have widely been used in bone tissue engineering. However, the underlying reason for their success in facilitating bone growth remain unclear. It was hypothesised that engineered bone tissue formation can be attributed to mechanical stimuli, which can be predicted in the tissue engineered construct. To test the hypothesis and draw conclusions as to how mechanical stimulation affects cell behaviour, a multidisciplinary approach using cell culture experiments and computational fluid dynamics (CFD) to simulate the complex flow within the spinner flask and scaffold was employed. Micro-computed tomography and histology showed that statically cultured human bone marrow derived stromal cells on silk fibroin scaffolds did not form extracellular matrix (ECM) or deposit minerals. However, constructs cultured at 60 rpm resulted in ECM formation and mineralisation, mainly at the bottom of the scaffold (bottom: 78±7%, middle: 17±5%, top: 5±2% of total mineralised volume). Culturing at 300 rpm led to a more homogeneously distributed ECM (bottom: 40±14%, middle: 33±1%, top: 27±14% of total mineralised volume). These observations were in agreement (Pearson correlation coefficient: 97%) with the computational simulations that predicted maximal scaffold mineralisation, based on wall shear stress stimulation, in the bottom at 60 rpm and in the main body at 300 rpm. Such combinations of CFD modelling and experimentation could advance our knowledge of the mechanical stimuli that cells experience in vitro and link them to biological responses.